A song for Pelagibacter. Using creative improvisation as a tool for novel science communication through the Ocean Science Jam - Whittaker, Geraint Rhys (Frontiers in Marine Science, 2024)
Sharing complex oceanic research in an accessible way with the public is being identified by scientific institutions, universities, governmental departments, and NGOs as a critical intervention in promoting better engagement with the sea. Art–science collaborations play an integral role in this. Traditionally, these involve pairing artists and marine scientists to work on a project which is then presented to an audience. Increasingly however more interactive relationships with the public are being seen as a beneficial way to merge art and scientific data. The Ocean Science Jam is such a project that brings musicians, artists, dancers, performers, and the public together to respond creatively in real time to visual and audio cues based on a theme related to marine scientists’ work. By mixing creativity with science in an integrative way the Ocean Science Jam not only acts as tool for public communication but also opens new ways for scientific data to be interpreted by non-scientists. This paper will explore this initiative from design to delivery highlighting the results of facilitating with the public moments where new responses to ocean science can be created through art. It will do so by combining the reflections of the creator of the Ocean Science Jam as well as feedback from the scientists and public who have participated. It will argue for the benefits of using improvisation and artistic co-creation for developing moments of embodied oceanic exchange and connection.